PENGARUH PENDIDIKAN KARAKTER DAN PENDIDIKAN AGAMA TERHADAP MORALSISWA MADRASAH TSANAWIYAH AL-MA’ARIF JIMBARAN BADUNG BALI - Fika Fatimatuzzahro; Atim S; Muhtadi (FAI- Undar, 2020)
Educational integrity in the formation of personality is not something that is not possible, but in it also contained the intention that the integrity of Islamic education in the formation of personality has a challenge that must be faced, especially in the various developments that occur at this time. In the formation of personality is not separate from the three elements of education, namely family, school, and society. Of the three elements there must be awareness of each party to complement each other in realizing education that can create people who have noble personalities. This study aims to find out: The influence of character education on student morale in MTs Al-Ma'arif Jimbaran B adung Bali in 2017-2018. The influence of religious education on students' morality in Al-Ma'arif Jimbaran Badung Bali MTs in 2017-2018 . The influence of character education and Islamic religious education on students' morality in MTs Al-Ma'arif Jimbaran Badun g Bali in 2017-2018.Research using approaches used is a quantitative approach used to answer the formulation of the research problem.Quantitative research is a research method that emphasizes objectively measurement aspects of social phenomena. In collecting data, this study uses questionnaire and document methods. Based on the results of the studyBased on the table above the level of significance of character education planting towards Morals shows the number 0.000 or probability <0001 or <0.05 so that there is a conclusion that there is a significant relationship between planting character education with Akhlaq Mahasiswa at MTs Al-Ma'arif Jimbaran Badung Bali. The level of significance of Islamic religious education towards the morality of students shows a number of 0,000 or p <0001 so that there is a conclusion that there is a significant relationship between Islamic religious education with Akhlaq Siswa at MTs Al-Ma'arif Jimbaran Badung Bali. The results of the data analysis of the planting of character education and Islamic religious education on the morality of students in Al-Ma'arif Jimbaran Badung Bali Mts are as follows: The R square number is 0.9 6 7 . This means 96 , 7% of the variation of student morality can be influenced by the variable planting character and Islamic religious education .And the rest is explained by other reasons.